Thanks for all the fish - Harris, Haden Dean (Rhodes University, 2026)
The study sought to investigate the exchange patterns amongst the artisanal fishers of Mahé, Seychelles, using gift exchange as a framework to explore the exchange patterns of the fisher groups of Seychelles, and what role these patterns play in marine resource management. This thesis used gift exchange patterns as a representation of the community structure, which in turn informs the potential of cooperative behaviour between members. Following the Maussian concept of “The Gift,” this research holds that these patterns are designed to fulfil the social obligations/norms that the participants hold with people based on their social relationships. Close-knit communities tend to have informally enforced social norms that foster cooperative behaviour. When structured on resource management, the social norms act as proxies to the potential for marine conservation compliance. This project took place over 30 days in May 2024 on the island of Mahé, Seychelles. Purposive sampling methods (cluster and convenience sampling) were used to find participants; data was gathered using exchange survey forms, semi-structured and informal interviews as well as participant observation. The results of this research found that the fisher's exchange patterns primarily focused on their own household and their crew. The likelihood of these exchanges occurring is directly influenced by the total amount the fishers caught, as fishers were found to be more generous only when they had a surplus of fish within their catch. The vast majority of participants held negative/indifferent opinions of the conservation strategies employed in Seychelles, which is a result of the inconsistency in the fisher's ability to provide for themselves through legal fishing activities. This paints a bleak picture for conservation within the Seychelles, as there is a lack of enforced social norms encouraging conservation practices with many motivators for non-compliance and ineffective formal law enforcement to dissuade potential poaching.
an exploration of exchange patterns amongst the artisanal fishers of Mahé, Seychelles
Keywords: Ceremonial exchange (http://id.loc.gov/authorities/subjects/sh85022128); Small-scale fisheries (http://id.loc.gov/authorities/subjects/sh2001000808); Marine resources conservation (http://id.loc.gov/authorities/subjects/sh85081260); Gift exchange (https://www.wikidata.org/wiki/Q23009552); Mahé (https://www.wikidata.org/wiki/Q219642)